Methodological innovations in the initial and permanent training of teachers - Oliveira, Maria Elizete Pereira Alencar; Barroso, Maria Cleide da Silva; Oliveira, Ciro Mesquita de (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
This study shows records that teachers make about their practices, experiences in light of the impact of changes in educational policy. The interest in knowing what teachers think about their practice began with a reflection aimed at a new praxis in which one of the obstacles to student learning is related to the teacher's precarious academic knowledge, with discrepancies between theory and practice, since theory it is important, but alone it is insufficient for the classroom. The aim of the study was to explore, through the literature, the need for alignment between theory and practice. The methodological procedures used for data collection included literature review, on-site observation and semi-structured interviews with teachers. The information collected was analyzed qualitatively, from the perspective of the authors who guided the theoretical foundation. It was concluded that it is up to the educator to perceive characteristics of the student and their interaction with the environment.